Effects of operating conditions in spray drying of recombinant bromelain - Amid, Azura; Othman, Muhd. Ezza Faiez; Jamaluddin, Mohd Jamil Aizat (AENSI, 2014)
The aim of the present study is to investigate the effect of operating parameter of a Buchi B290 mini spray dryer towards specific activity of recBromelain. Using Response Surface Methodology (RSM), face centred central composite design (FCCCD) was tabulated for optimization. Optimization process was conducted by varying the inlet air temperature (°C), gas flow height (mm) and pump settings (%) of the laboratory Buchi B290 Mini Spray Dryer to obtained optimal spray drying operating processes recovering high recBromelain specific activity as response. Results showed that the optimized process parameter having 126 °C air inlet temperature, 42 mm gas flow height and 12 % feed pump setting resulted in 0.119 ± 0.003 U/mgprotein of spray dried recBromelain with R2 of 90.12% thus this model was found to be significance and reliable.